DEVELOPMENT OF STUDENTS' CONSCIOUS NEED FOR A HEALTHY LIFESTYLE DURING HIGHER EDUCATION - Mardonova Saodat Muzaffarovna (Journals Park Publishing, 2024)
The development of students' conscious need for a healthy lifestyle during higher education is crucial for fostering long-term wellness and academic success. This study examines the factors that influence the adoption of healthy behaviors among university students and the role of higher education institutions in promoting a health-conscious environment. Through a mixed-methods approach, including surveys, interviews, and intervention programs, the research identifies key determinants such as awareness, motivation, and institutional support. The findings highlight the importance of integrating health education into the curriculum, providing accessible resources, and creating a supportive community that encourages healthy lifestyle choices. The study concludes with recommendations for policy makers and educational leaders to enhance health promotion strategies in higher education settings.
Keywords: healthy lifestyle, higher education, student wellness, health education, behavior change, institutional support.